2014
DOI: 10.5194/acp-14-11117-2014
|View full text |Cite
|
Sign up to set email alerts
|

The decreasing albedo of the Zhadang glacier on western Nyainqentanglha and the role of light-absorbing impurities

Abstract: Abstract.A large change in albedo has a significant effect on glacier ablation. Atmospheric aerosols -e.g. black carbon (BC) and dust -can reduce the albedo of glaciers and thus contribute to their melting. In this study, two main themes were explored: (1) the decrease in albedo of the Zhadang glacier on Mt. Nyainqentanglha between 2001 and 2012, as observed by the Moderate Resolution Imaging Spectroradiometer (MODIS) on-board the Terra satellite, and the correlation of this albedo with mass balance; and (2) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 50 publications
(39 reference statements)
5
107
2
Order By: Relevance
“…Studies on the TP indicate that BC has been a significant contributing factor to the observed cryospheric change Ming et al, 2009;Niu et al, 2017;Xu et al, 2009;Yang et al, 2015;Zhang et al, 2017) and a major forcer of climate change Ji, 2016). Observations and simulations also found that dust deposition on snow/ice can change the surface albedo and perturb the surface radiation balance (Ji, 2016;Qu et al, 2014), resulting in a decrease of 5-25 mm snow water equivalent (mm w.e.) over the western TP and Himalayas (Ji, 2016).…”
mentioning
confidence: 99%
“…Studies on the TP indicate that BC has been a significant contributing factor to the observed cryospheric change Ming et al, 2009;Niu et al, 2017;Xu et al, 2009;Yang et al, 2015;Zhang et al, 2017) and a major forcer of climate change Ji, 2016). Observations and simulations also found that dust deposition on snow/ice can change the surface albedo and perturb the surface radiation balance (Ji, 2016;Qu et al, 2014), resulting in a decrease of 5-25 mm snow water equivalent (mm w.e.) over the western TP and Himalayas (Ji, 2016).…”
mentioning
confidence: 99%
“…However, although the values were relatively high, they were at the same level or lower than the estimates for an albedo reduction of 28 % by BC and 56 % by dust in clean ice samples and of 36 % by BC and 29 % by dust in aged snow samples, reported by Qu et al (2014) for surface samples from the Zhadang glacier, China. Simulation results by Ming et al (2013) showed BC, dust, and grain growth to reduce the broadband albedo by 11, 28, and 61 %, respectively, in a snowpack in central Tibet.…”
Section: Snow Albedo Reductionmentioning
confidence: 57%
“…The results suggest that BC was the dominant forcing factor, rather than dust, influencing glacial surface albedo and accelerating glacier melt. BC was found to play an important role in forcing in the northern Tibetan Plateau (Li et al, 2016), whereas in the central Tibetan Plateau and the Himalayas, dust played a more important role (Qu et al, 2014;Kaspari et al, 2014). The MAC value affected the albedo more in the visible range than at 1.2 µm (nearinfrared) wavelength (Fig.…”
Section: Snow Albedo Reductionmentioning
confidence: 99%
See 2 more Smart Citations